Employee Engagement and Work–Life Balance Effects on Turnover Intention: The Intervening Role of Rewards among Gen Z Employees (International Forum of Researchers and Lecturers, 2026)
This study investigated how employee engagement and work–life balance influenced turnover intention, with rewards examined as an intervening mechanism, among Generation Z employees in a state-owned enterprise context. A quantitative explanatory design was applied using a census approach involving all 36 Generation Z employees at PT PLN (Persero) Pematangsiantar. Data were collected through structured questionnaires measured on a five-point Likert scale and were analyzed using multiple regression and mediation-based path analysis in SPSS. The findings showed that employee engagement and work–life balance significantly predicted perceived rewards, and all three variables exerted significant effects on turnover intention. Moreover, rewards partially mediated the effects of employee engagement and work–life balance on turnover intention, indicating that positive work experiences reduced employees’ intention to leave when they were reinforced by fair and meaningful reward practices. However, the small sample size limited the generalizability of the findings beyond the organizational setting studied. This study contributes by demonstrating that retention of Generation Z employees is shaped not only by psychological attachment and work–life balance, but also by how organizations institutionalize recognition and value exchange through reward systems, particularly in public service and state-owned enterprises.